Three new species of Peltaea (Malvaceae, Malvoideae) from the cerrado of Brazil - Fernandes-Júnior, Aluisio J.; Esteves, Gerleni L. (Phytotaxa, 2016)
Three new species of Peltaea are described from the cerrado of Brazil: P. brasiliana from Distrito Federal, P. rupestris from the state of Minas Gerais and P. stellata from the state of Tocantins. Illustrations, comments on morphology, taxonomic relationships, and phenology are provided, as well as assessments of conservation status of the new species.